2022
DOI: 10.1007/s12020-022-03176-8
|View full text |Cite
|
Sign up to set email alerts
|

The combination of BRAFV600E mutation and Chinese Thyroid Imaging Reporting and Data System is helpful in the management of AUS/FLUS thyroid nodules

Abstract: Purpose To explore the utility of the BRAF V600E mutation in combination with Chinese Thyroid Imaging Reporting and Data System (C-TIRADS) in the management of atypia of undetermined signi cance/follicular lesion of undetermined signi cance (AUS/FLUS) thyroid nodule (TN).Methods 138 AUS/FLUS TNs in 129 patients were included. Each TN underwent preoperative BRAF V600E mutation analysis and was classi ed using the C-TIRADS. Histopathologic diagnosis served as reference standard.Results 46 benign TNs and 92 malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Studies have shown that the BRAF V600E gene mutation exhibits high specificity and general sensitivity for diagnosing PTC ( 13 , 14 ). In some studies, the combination of BRAF V600E and RSSs was used for the diagnosis of thyroid nodules ( 15 , 16 ). The general approach involved performing a BRAF V600E test on all thyroid nodules and diagnosing those with positive BRAF V600E or RSSs results as positive while diagnosing those with negative results for both markers as negative.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the BRAF V600E gene mutation exhibits high specificity and general sensitivity for diagnosing PTC ( 13 , 14 ). In some studies, the combination of BRAF V600E and RSSs was used for the diagnosis of thyroid nodules ( 15 , 16 ). The general approach involved performing a BRAF V600E test on all thyroid nodules and diagnosing those with positive BRAF V600E or RSSs results as positive while diagnosing those with negative results for both markers as negative.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported that the diagnostic accuracy of BRAF V600E gene mutation combined with enhanced computed tomography (CT) was significantly improved relative to enhanced CT alone [21]. In addition, compared with only TI-RADS, the combination of TI-RADS and BRAF V600E gene mutation detection contributed to select the more appropriate management for the patients with atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) thyroid nodule [22].…”
Section: Introductionmentioning
confidence: 99%